Preparation of Polycaprolactone-Graphene Oxide Hydrogel as Potential Drug Delivery Carrier - Dalagan, J.; Barros, H. (Asian Journal of Chemistry, 2021)
Polycaprolactone-graphene oxide (PCL-GO) hydrogel composite was prepared using a facile method and characterized by Fourier transform Infrared (FTIR) and scanning electron microscopy (SEM). The swelling capacity of the hydrogel at varying temperature and equilibration time was also determined. IR analysis revealed a shifting of bands, which indicates H-bonding interactions between polycaprolactone and graphene oxide. Characteristic peaks of graphene oxide at 3500 cm-1 for -OH stretching and peaks of polycaprolactone at 1456, 1370, 1304 cm-1 for CH2 bending vibrations were observed. SEM images validated IR results with the occurrence of larger hollow regions, pores and insets indicating reaction of OH groups with the polymeric chains. The swelling ratio of the PCL-GO hydrogel was higher than polycaprolactone and graphene oxide at 4 h and 8 h equilibration time. The swelling ratio of PCL-GO at 40 ºC and 12 h equilibration time was 4.3, which was the highest among the swelling ratios. These data could imply that the PCL-GO prepared has the potential to be a potential drug carrier.